The Impact Of Government Enhancement Programmes On SME Performance In Malaysia - Pairan, Najatul Haya (2018)
SME has gained attention in the design of development policy plans by the government from time to time. Under the Eleventh Malaysian Plan (2016-2020) presented by prime minister of Malaysia, to enable SMEs meet the business challenges in the global competitive environment, the government allocated totaling RM495.2 million to 760 Bumiputera SMEs to help them in all aspects of their operations. The government has been expanding and diversifying its supports and incentives through several assistance programmes such as innovation programme, partnership, market expansion etc. These programmse are vital in order to ensure that SMEs are able to sustain their economic development although lacking in terms of resources. Therefore, this study has reviewed and analysed the impact of government enhancement programmes (GEPs) towards SME performance in Malaysia. Three objectives are used as guidelines in conducting this thesis which are to determine the types of government enhancement programme that can improve SME performance and competitiveness in the global market, to measure the relationship of government enhancement programme on SMEs performance and to analyse the most effective of government enhancement programme in improving the SME performance. This research has examined the effectiveness of GEP based on four main dimensions consist of technology and infrastructure support, marketing support, product development support and strategic alliance support. A research framework for GEP has been developed and in this framework all factors are being tested in order to determine their influence on the performance of SMEs. This thesis has applied quantitative methodology using questionnaire as the research instrument. The questionnaire was distributed to 550 SMEs from manufacturing sector that have participated in the programmes offered by selected agencies in Melaka, Kuala Lumpur and Johor. Data collected were analysed using statistical package for the social sciences SPSS version 20. The results found that all GEPs factors outcomes serve as the key facilitating role in achieving the higher performance of SME. However, product development support programme (PDS) recorded the most effective factor and significantly influence to the performance of SMEs with beta value of unstandardized coefficient at 0.340. This is due to the various reasons such as the unique characteristics of new product in market will fulfill the demand and increase the satisfaction of customers. Finally, this research makes several contributions and provides further insights on the impacts of GEPs. From the industrial viewpoint, this study provides many valuable discoveries that can be used to the benefit of the respective industries such as expand their market and reduce the R&D costs. An important implication of this study to the government, this research will facilitate the government agencies to develop or improve the enhancement programmes to better suit the needs of SMEs towards producing positive outcomes or effect for increased performance in SMEs industry.